Crystal structure of bromido[hydridotris(3-tert-butyl-5-isopropylpyrazolyl)borato-κ3 N,N′,N″]copper(II), C30H52BBrCuN6 - Fujisawa Kiyoshi; Tiekink Edward R.T. (Zeitschrift für Kristallographie - New Crystal Structures)
C30H52BBrCuN6, monoclinic, P21/n (no. 14), a = 9.4265(3) Å, b = 17.4945(5) Å, c = 20.2269(5) Å, β = 99.926(3)°, V = 3285.73(17) Å3, Z = 4, R gt(F) = 0.0387, wR ref(F 2) = 0.1055, T = 184 K.